Efeitos da restrição alimentar sobre marcadores bioquímicos da remodelação óssea e sobre as propriedades biométricas, biofísicas, densitométricas, bioquímicas e biomecânicas de fêmures e vértebras de ratos de diferentes idades - Biffe, Bruna Gabriele (2016)
The food restriction promotes adaptive mechanisms that have beneficial effects on diseases and longevity. Also, bone is target of effects provided by the reduction of diet intake. However, there are controversies about the responses that this intervention can result on bone quantity and quality. The aim of this study was to evaluate the effect of food restriction 30% on bone parameters of femurs and vertebrae from rats of different ages. Male Rattus novegicus albinus rats, Holtzman lineage, aged 38 days, 4 and 16 months of age were used. The animals were divided into six groups (n=8-10 per group), three being control groups (C38, C4 and C16) and three groups on restricted diet (R38, R4 on R16). The control animals had free access to food and water. The restricted animals were submitted to food restriction of 30% being fed with 70% of the ad libitium consumption of the control group. The experimental period for all groups was 6 weeks. Analysis was performed in biochemical markers of formation (osteocalcin) and bone resorption (TRAP), and in parameters biometric (length, largest and smallest diameter of the femur, vertebral height), biophysical (wet, dry and immersed weight, and of ashes, bone volume, bone and mineral density, percentage of water, mineral and organic matter), biochemical (calcium and phosphorus content), densitometric (aDMO of the femur [all bone, proximal epiphysis, diaphysis and epiphysis distal] and the vertebra), biomechanical properties (maximum load, maximum load until fracture, displacement until fracture, femoral tenacity and stiffness; spinal maximum load, tenacity and stiffness), in addition to body mass and abdominal fat mass. The body mass and fat mass gain in restricted animals was lower than that of animals which had food ad libitium. The food restriction in animals with 38 days and 4 months of age presented decreased bone formation, while the ones with 16 months presented decreased bone resorption. Food restriction induced reduction of the biometric parameters, biophysical weights, femoral bone volume and calcium and phosphorous content in the restricted group aged 38 days. In addition, femoral length and calcium content were reduced in the restricted group aged 4 months. The restricted diet induced reduced areal density in femurs and femoral diaphyseal of 38 days rats, and increased aDMO of femoral epiphysis proximal from 16 months rats. The femoral biomechanical properties were not affected by the food restriction diet in any of the experimental groups. As regards the vertebral analysis, vertebral height, wet weight, immersed weight, bone volume and percentage of water were lower in the restricted group aged 38 days. Moreover, vertebral height was reduced in the restricted group aged 4 months. However, mineral density, percentage of mineral matter and maximum load were higher in the restricted group aged 38 days. The areal density, vertebral tenacity and stiffness were not altered by the food restriction. The food restriction diet resulted in damage to femoral bone development with remarkable loss in prepubertal rats, inconsistent alterations in young adult rats and potential benefits to bones of elderly rats. In addition, restriction had a positive influence on vertebral bone properties.